Meningkatkan Motivasi Belajar dan Hasil Belajar Siswa pada Pelajaran Matematika Melalui Penerapan Model Contextual Teaching and Learning [Improving Students' Learning Motivation and Learning Outcomes in Mathematics Through Implementation of Contextual Teaching and Learning Model] - Yohana Iskandar Darmawan (Jurnal Teropong Pendidikan, 2021)
In this research study, teacher takes improvement action by using contextual teaching and learning to solve the students’ learning motivation and learning outcomes problems. This study aims to: (1) describe the implementation of contextual teaching and learning to improve students’ learning motivation and students’ learning outcomes; (2) analyze the development of students’ learning motivation; (3) analyze the development of students’ learning outcomes; (4) identify the obstacles during the implementation process and how to solve them. This study is called a Classroom Action Research (CAR) carried out in three cycles. The subjects were 21 students of class VI D Harapan Bangsa Primary School. Data was collected by using observation, field notes, interviews, written test, and analyzed with descriptive qualitative. The result showed: (1) the learning process is based on the 7 steps of the implementation of contextual teaching and learning; (2) there is 35% increase in students’ learning motivation; (3) there is 34% increase in students’ learning outcomes; (4) teacher overcomes the obstacles of the limitation of time, students who don’t work actively in groups, students who have less motivation and learning outcomes, and technical problem in learning video by creating a better time management, giving the motivation for students to participate actively in question and answer, including in discussion process, and downloading the learning video during the improvement action planning.